Desain dan Visualisasi Media Edukasi Rumah Adat Nusa Tenggara Timur (NTT) menggunakan Teknologi Augmented Reality - Delia Marisa Wulandari Suyitno Putri; Sumarlin Sumarlin; Hasibun Asikin (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
The low use of interactive learning media to introduce local culture has limited students' interest and understanding of the traditional houses of East Nusa Tenggara (NTT). This study aims to design and develop interactive educational media based on Augmented Reality (AR) to help students understand the form, function, and philosophy of traditional NTT houses in a more engaging and interactive way. The method used in this study is the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The system was developed using ZapWorks Studio for implementing AR technology and Blender for creating 3D models of traditional houses. The results show that the AR-based educational media is capable of displaying visualizations of traditional NTT houses in the form of three-dimensional objects, along with educational information and interactive quiz features in real time. This media can be used as an engaging and interactive learning tool, helping to increase student interest in learning and support the preservation of local culture in the digital age.